2013
DOI: 10.1155/2013/275753
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Diversity and Insignificant Interspecific Differentiation in Opisthopappus Shih, an Endangered Cliff Genus Endemic to the Taihang Mountains of China

Abstract: Opisthopappus Shih is endemic to the Taihang Mountains, China. It grows in the crevice of cliffs and is in fragmented distribution. This genus consists of two species, namely, O. taihangensis (Ling) Shih and O. longilobus Shih, which are both endangered plants in China. This study adopted intersimple sequence repeat markers (ISSR) to analyze the genetic diversity and genetic structure from different levels (genus, species, and population) in this genus. A total of 253 loci were obtained from 27 primers, 230 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
3
7
1
Order By: Relevance
“…High genetic diversity in populations of organisms is a successful strategy that facilitates their adapting to various habitats and environmental conditions [41,42] toward increasing their effective colonization in new habitats [42][43][44]. In this study, high genetic diversity was observed in O. longilobus or O. taihangensis (Table 1), which was consistent with previous research by ISSR [36] and SRAP [38] markers. This was similar to other endemic and endangered species, such as Helianthemum songaricum [45], Sinowilsonia henryi [46], and Taihangia rupestris [47].…”
Section: Genetic Differentiation Results From Geographic Topology Andsupporting
confidence: 92%
See 1 more Smart Citation
“…High genetic diversity in populations of organisms is a successful strategy that facilitates their adapting to various habitats and environmental conditions [41,42] toward increasing their effective colonization in new habitats [42][43][44]. In this study, high genetic diversity was observed in O. longilobus or O. taihangensis (Table 1), which was consistent with previous research by ISSR [36] and SRAP [38] markers. This was similar to other endemic and endangered species, such as Helianthemum songaricum [45], Sinowilsonia henryi [46], and Taihangia rupestris [47].…”
Section: Genetic Differentiation Results From Geographic Topology Andsupporting
confidence: 92%
“…Between O. taihangensis and O. longilobus, several morphologica [30,34,35] and genetic variations [36][37][38][39][40] have been observed. Nevertheless, the interspecific hybridization of these two species have never been reported.…”
Section: The Southern Taihang Mountains Have Existed As a Major Boundmentioning
confidence: 99%
“…Additionally, with the rapid development of various molecular markers such as RFLP, RAPD, ISSR, simple sequence repeat (SSR), SR, AFLP and single nucleotide polymorphism (SNP), the genetic diversity analyses of Opisthopappus Shih populations were carried out to obtain more comprehensive information and data about genetic differentiation and variation. The results revealed abundant genetic diversity in populations but low level of genetic differentiation among populations and confirmed that the genetic difference of the species mainly existed within populations ( Guo et al, 2013 ). Meanwhile, the cluster analysis based on the genetic distance showed that O. longilobus populations were not monophyletic group, and the remaining populations of O. longilobus were gathered with O. taihangensis populations, which indicated that gene exchange or interspecific hybridization might occur between the two species ( Wang et al, 2015 ).…”
Section: Introductionsupporting
confidence: 55%
“…Population genetic analysis in Opisthopappus Shih have been carried out by using various molecular markers, such as RFLP, RAPD, ISSR, cpSSR, and SRAP ( Guo et al, 2013 ; Wang, 2013 ; Wang and Yan, 2013 ). However, no definitive conclusions were established to illustrate interspecific differences and confirm the taxonomy status between O. longilobus and O. taihangensis .…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of our results with other studies is problematic, since genetic diversity depends on numerous factors such as life-history traits, geographic range, and even the type of molecular method used (Nybom 2004). Nevertheless, in the group of endemic taxa of rocky/mountainous habitats we find several examples of species characterized by high genetic variability, for example Aster pyrenaeus (Escaravage et al 2011), Astragalus albens (Neel 2008), Campanula sabatia (Federica et al 2012) or representatives of the genus Opisthopappus (Guo et al 2013). Further examples of species with high levels of genetic variability in the population are found in more widespread alpine species having topographically isolated populations inhabiting a harsh environment, such as Table 1 Fig .…”
Section: Discussionmentioning
confidence: 63%